Peptide and protein chemistry approaches to study the tumor suppressor protein p53. Issue 28 (4th July 2022) - Chatterjee, Champak; Singh, Sumeet K.
Abstract : The tumor suppressor and master gene regulator protein p53 has been the subject of intense investigation for several decades due to its mutation in about half of all human cancers. Abstract : The tumor suppressor and master gene regulator protein p53 has been the subject of intense investigation for several decades due to its mutation in about half of all human cancers. However, mechanistic studies of p53 in cells are complicated by its many dynamic binding partners and heterogeneous post-translational modifications. The design of therapeutics that rescue p53 functions in cells requires a mechanistic understanding of its protein–protein interactions in specific protein complexes and identifying changes in p53 activity by diverse post-translational modifications. This review highlights the important roles that peptide and protein chemistry have played in biophysical and biochemical studies aimed at elucidating p53 regulation by several key binding partners. The design of various peptide inhibitors that rescue p53 function in cells and new opportunities in targeting p53-protein interactions are discussed. In addition, the review highlights the importance of a protein semisynthesis approach to comprehend the role of site-specific PTMs in p53 regulation.